Life and Death in Diary of A Mad Old Man by Junichiro Tanizaki, Aku by Chairil Anwar, the Jilting of Granny Weatherall by Kathrene Anne Porter and the Tinkers by Paul Harding - Ningsih, Yanti Rahayu; Indriawati, Arlisa (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2019)
Even every work of arts especially in literature has their own unique story style yet its also has similarities in the idea or problems of human being. The similarities appear on their works because they share some common aspects of life which is also called as the intertextuality. Themes and motives in work of arts are similar because of the universal consciousness among the authors. And by these works Diary of a Mad Old Man by Junichiro Tanizaki, Aku by Chairil Anwar, The Jilting of Granny Weatherall by Kathrene Anne Porter and The Tinkers by Paul Harding deal with the same theme about life and death. Moreover, three main characters also in the same age, they are old people who fought their life before the death toke it away. The analysis is using qualitative method to evaluate the similarities and the differences concept of life and death and also to able to found out any correlation of each work related with the intertextuality among them